Pengaruh Model Pembelajaran Contectual Teaching Learning terhadap Kemampuan Menulis Siswa di Madrasah Ibtidaiyah - Al Ihwanah; Amir Rusdi; Aquami Aquami (Universitas Islam Negeri Raden Fatah Palembang, 2022)
Current education teachers are required to work harder in improving student learning competence. This relates to how the teacher's efforts to convey learning to students. This study focuses on students' ability to write story texts using the Contextual Teaching Learning model. This research was conducted in class IV MI Qur'aniah Palembang. The research method used is a type of quantitative experimental research. The purpose of this study was to determine the effect of the Contextual Teaching and Learning learning model on the ability to write stories. Data collection was carried out using the pretest and posttest test techniques to a predetermined sample, namely class IV students with a total of 15 students. To determine the influence between the two variables, the researchers analyzed the data by using the Paired Sample t-test using the SPSS 20 application. From the analysis, it was found that the sig value (2 t-tailed) < 0.05 was 0.000 < 0.05. In addition, a t-count of 14.480 was also obtained. t-table level of significance (α/2) equals 0.025 = 2.144. So the results of the hypothesis test are t-count values ​​> t-table values ​​(14.480 > 2.144). So it can be concluded that there is a difference in the average pretest and posttest learning outcomes and there is a difference in the frequency of pretest and posttest, which means that there is an effect of using the Contextual Teaching and Learning learning model on students' ability to write story texts.